Reading in Russia - A cura di: Damiano Rebecchini (Ledizioni, 2014)
Reader, where are you?", wondered, in the mid-1880s, Mikhail Saltykov-Shchedrin, one of the Russian writers that paid the most attention to the readership of his time. Saltykov-Shchedrin's call did not go unanswered. Over the past two centuries, various disciplines - from the social sciences to psychology, literary criticism, semiotics, historiography and bibliography